The Effect of Special Exercises in the Development of Some Visual Abilities and the Accuracy of Some Basic Skills of the Young in the Handball - Thaerah Abdul Jabbar Saleh (Journal of Global Pharma Technology, 2016)
The problem of research is the lack of use of some trainers for visual exercises during the training modules and do not have great importance in their training curriculum as it is for the physical, skill and planning aspects, and thus the objectives of the research are as follows:Develop special exercises to develop some visual abilities and the accuracy of some of the basic skills of beginner's handball.Knowing the impact of special exercises in developing some of the visual abilities of the emerging handball players.Knowing the effect of special exercises in developing the accuracy of some of the basic skills of beginner's handball.Either Research HypothesesThere is a significant impact of special training in developing some visual abilities of the emerging handball players. There is a significant effect of special exercises in developing the accuracy of some of the basic skills of beginner's handball. The researchers adopted the experimental approach in the design of the two equal groups with Pre and Post testing through the research society represented by the players of the specialized center of handball at Al-Qasim Sports Club. The number of (40) player was randomized. The random number of 16 players was divided into two equal groups, And the tests used in the visual abilities and skill handball were conducted Pretests, and then applied visual exercises for the experimental group by combining them with the curriculum prepared by the trainer (3) units per week for a period of (8) weeks, and then conducted After the data were obtained from the Pre and Posttests where the researcher treated them statistically to extract the results. The results were presented, analyzed and discussed according to research objectives, the most important conclusions reached by the researchers in:There is an evolution of the experimental group in all visual and technical tests of the hand pulley except the test (Perception of the depth of vision) as well as the control group, except for the Perception of the depth of vision and the test of the accuracy of handling from the head level by the field of vision. Visual training is futile in the latest development in the Perception of the depth of vision and accuracy of the performance of the correction of the jump field of vision of the two groups.Keywords: Special exercises, Visual abilities and accuracy.